1975
DOI: 10.1073/pnas.72.9.3575
|View full text |Cite
|
Sign up to set email alerts
|

Brain tryptophan hydroxylase: purification of, production of antibodies to, and cellular and ultrastructural localization in serotonergic neurons of rat midbrain.

Abstract: Tryptophan hydroxylase [EC 1.14.16.4; Ltryptophan, tetrahydropteridine:oxygen oxidoreductase (5-hydroxylating)], the enzyme catalyzing the rate-limiting step in the biosynthesis of serotonin, was purified 79-fold from the region of the raphe nucleus of rat midbrain by sequential column chromatography and disc-gel electrophoresis. In electrophoresis three bands were distinguished, A, B, and C, which, when separated and submitted individually to electrophoresis, reproduced the same three bands. Bands A and C wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
5

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 26 publications
2
34
0
5
Order By: Relevance
“…The action through 5-HT 2A receptors is probably also related to 5-HT dopamine interaction because blocade of 5-HT 2A receptors on dopaminergic neurons could result in higher release of dopamine which could influence 5-HT synthesis [35]. The tryptophan hydroxylase (TPH) is "mostly" expressed in the cell bodies found in raphe nuclei (e.g., [36]), but there is also substantial evidence that TPH is present in the serotonergic terminals [62,18,59], and that the synthesis of 5-HT is occurring in those terminals (e.g., [49,33,11,51]). …”
Section: Discussionmentioning
confidence: 99%
“…The action through 5-HT 2A receptors is probably also related to 5-HT dopamine interaction because blocade of 5-HT 2A receptors on dopaminergic neurons could result in higher release of dopamine which could influence 5-HT synthesis [35]. The tryptophan hydroxylase (TPH) is "mostly" expressed in the cell bodies found in raphe nuclei (e.g., [36]), but there is also substantial evidence that TPH is present in the serotonergic terminals [62,18,59], and that the synthesis of 5-HT is occurring in those terminals (e.g., [49,33,11,51]). …”
Section: Discussionmentioning
confidence: 99%
“…The three enzymes catalyze similar hydroxylation reactions and share a distinctive requirement for tetrahydrobiopterin (BH 4 ) and non-heme ferrous iron as cofactors (2). Studies of TPH have been hampered by the extreme instability of the enzyme (5)(6)(7)(8)(9)(10)(11) and the difficulty in obtaining high levels of purified active enzyme from either native or heterologous sources (10 -17). Sequence analyses of TPH cDNAs derived from mammalian and other vertebrate species (13, 18 -23) revealed that TPH shares high overall sequence homology with the other two members of the hydroxylase family (1,2).…”
mentioning
confidence: 99%
“…After 3 weeks' growth, cultures were fixed in picric acid/formalin and processed as whole mounts. The sections of rat intestine, the whole mounts of longitudinal muscle with attached'myenteric plexus from guinea pigs, and the cultures from mice were incubated with rabbit antiserum to tryptophan hydroxylase (purified from raphe nuclei of rat brain), goat antiserum to rabbit IgG, and peroxidase-antiperoxidase complex (18,20). Peroxidase activity was then localized with 3,3'-diaminobenzidine and hydrogen peroxide (18,20).…”
mentioning
confidence: 99%
“…The sections of rat intestine, the whole mounts of longitudinal muscle with attached'myenteric plexus from guinea pigs, and the cultures from mice were incubated with rabbit antiserum to tryptophan hydroxylase (purified from raphe nuclei of rat brain), goat antiserum to rabbit IgG, and peroxidase-antiperoxidase complex (18,20). Peroxidase activity was then localized with 3,3'-diaminobenzidine and hydrogen peroxide (18,20). In this bridge technique, the unlabeled rabbit antibody to tryptophan hydroxylase combines with the enzyme in the tissue, the goat antiserum bridges the rabbit antibody to the peroxidase-antiperoxidase complex, and the peroxidase activity localizes the tryptophan hydroxylase.…”
mentioning
confidence: 99%